A pilot study to evaluate the efficacy of mucoadhesive (Aphtogel) in the treatment of oral minor aphthous ulcers - Gholamreza Jahanshahi; Mohsen Saniei (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Triamcinolone has been introduced as the treatment of choice in symptomatic treatment of oral aphthous ulcers in the medical literature. One of the major challenges in drug therapy all over the world is how to deliver the drug to target tissues, and how to best deliver minimal amounts of the drug to the injured organ. The aim of this pilot study was to determine minimum dose of the required drug effective on the oral minor aphthous ulcers and evaluate its effectiveness. Materials and methods: In this double-blind pilot clinical trial, a new form of muccoadhesive with the dual aim of dressing of and concentration of the drug on the aphthous ulcers was designed and manufactured by adding triamcinolone to muccoadhesive base. The drug was applied to 40 patients with no systemic conditions or previous drug therapy. Only 23 of the patients cooperated during the whole trial and could provide documented data. Fourteen patients received the drug and 9 received a placebo. Pain severity was evaluated by VAS scale and maximum diameters of ulcers were measured in millimeter. Data were analyzed by SPSS software and Mann-Whitney test (α=0.05).Results: In patients who received the drug the diameter (p value = 0.026) and pain severity (p value = 0.043) were significantly less during the second appointment in comparison with the patients receiving placebo. However, during the third appointment there were no significant differences between the two groups (p value < 0.05).Conclusion: According to the results of this pilot clinical trial, addition of triamcinolone to the base of muccoadhesive has a significant effect on diminishing pain severity and diameter of oral ulcers in the short term in comparison to placebo and this approach can effectively be used to decrease pain severity accelerate ulcer healing. Key words: Aphthous, double-blind method, placebo effect, stomatitis.